Analysis of a Relaxation Scheme for a Nonlinear Schrödinger Equation Occurring in Plasma Physics - Oelz, Dietmar; Trabelsi, Saber (Mathematical Modelling and Analysis, 2014)
This paper is devoted to the analysis of a relaxation-type numerical scheme for a nonlinear Schrödinger equation arising in plasma physics. The scheme is shown to be preservative in the sense that it preserves mass and energy. We prove the well-posedness of the semidiscretized system and prove convergence to the solution of the time-continuous model.